Pengaruh Bahan Baku, Tenaga Kerja dan Kemampuan Manajerial Terhadap Jumlah Produksi Tahu - Azizah, Nur; Setiaji, Khasan (Universitas Negeri Semarang, 2021)
One most influential things about the total production is the factors of production.This research aims to determine the effect of raw materials, labor, and managerial ability on the total production of tofu in Adiwerna Village, Adiwerna district, Tegal. The population in this study were tofu craftsmen in Adiwerna Village, Adiwerna district, Tegal Regency in the amount of 319 craftsmen and obtained sample of 76 people using simple random sampling. Data collection tool was the questionnaire or questionnaire method. analysis. The result of the research shows that there is influence between raw materials, labor, and managerial ability to total production either simultaneously or partially. The simultaneous effect of 0,518 or 59,1% whereas 40,9% is explained by other factors. Partially raw material , labor, and managerial ability to the total production are 14,67%, 16,31%, and 7,73%. The conclusion of this research is there is positive and significant influence between raw materials, labor, and managerial ability to total production. The suggestions of this study are Tofu craftsmen must pay attention to the availability of raw materials when the prices increase, they can augment labor productivity well and improve their capabilities so that the level of production can be maintained both in quantity and quality.